Reform, Growth, and Poverty in Vietnam - Dollar, David (World Bank, Washington, D.C., 2013)
Vietnam grew rapidly in the 1990s, and yet by many measures it has poor economic institutions. Dollar seeks to explain this apparent anomaly. Between the 1980s and 1990s Vietnam carried out significant economic reforms, notably stabilization, the introduction of positive real interest rates, trade liberalization, and initial property rights reform in agriculture. Relating these changes to the empirical growth literature, the author finds that Vietnam's growth acceleration is about what would be predicted. Conditional convergence also suggests that the country's high growth rate will decelerate unless further reforms are taken. The author then looks at the level of institutional and policy development in Vietnam compared with other emerging market economies. While Vietnam's policies have improved, they did so starting from a very low base. So, it can be simultaneously true that Vietnam's policies have improved a lot and yet are rather poor in comparative perspective. A comparison of governance indicators, financial sector issues, and the infrastructure of international integration reveals serious institutional weaknesses in Vietnam that need to be addressed if a high growth rate is to be sustained.